2004
DOI: 10.2202/1534-5998.1114
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stock Prices, House Prices and Consumption in OECD Countries

Abstract: This paper analyzes the relationship between stock prices, house prices and consumption using data for 16 OECD countries. The panel data analysis suggests that the long-run responsiveness of consumption to permanent changes in stock prices is higher for countries with a market-based financial system than for countries with a bank-based financial system. Splitting the sample into the 1980s and 1990s further shows an increased sensitivity in the 1990's of consumption to permanent changes in stock prices for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
148
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(172 citation statements)
references
References 22 publications
18
148
3
3
Order By: Relevance
“…5 Ludwig and Sløk (2004), Catte et al (2004) and Cardarelli et al (2008) bring some evidence on this, which I confirm and extend below.…”
Section: Ecb Working Paper Series No 1117supporting
confidence: 52%
See 3 more Smart Citations
“…5 Ludwig and Sløk (2004), Catte et al (2004) and Cardarelli et al (2008) bring some evidence on this, which I confirm and extend below.…”
Section: Ecb Working Paper Series No 1117supporting
confidence: 52%
“…Cross-country comparative work includes Bertaut (2002), Ludwig and Sløk (2004), Catte et al (2004), Case et al (2005) and Labhard et al (2005). The implications of these papers are constrained by data limitations, which I try to alleviate.…”
Section: Ecb Working Paper Series No 1117mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Almeida et al (2006) have reported evidence that the sensitivity of house prices and mortgage borrowings to income shocks is higher in countries with higher loan-to-value ratios. Ludwig and Sløk (2004) and Carroll et al (2006) have emphasized that the long-run responsiveness of consumption to permanent changes in housing wealth is higher for countries with a market-based than for countries with a bank-based financial system. According to Catte et al (2004), strong impacts of real house prices on consumption can be detected especially in countries that have large, efficient and responsive mortgage markets.…”
Section: Introductionmentioning
confidence: 99%